PENGARUH KONVEKSITAS TERHADAP SENSITIVITAS HARGA JUAL DAN DELTA-NORMAL VALUE AT RISK (VAR) PORTOFOLIO OBLIGASI PEMERINTAH MENGGUNAKAN DURASI EKSPONENSIAL - Putri Devitasari; Di Asih I Maruddani; Puspita Kartikasari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2022)
Bonds are one of the investment instruments issued by the issuer as proof of debt. Bond investment is relatively safe, but it is possible for investors to experience losses. Investors should always consider that trading a bond is always risky. One of the important bond risks is interest risk. The concept of duration can only explain well for small changes in interest rates but cannot explain well for large changes in interest rates. The estimation of the duration concept will have a larger calculation error with the greater changes in market interest rates that occur so it is necessary to add convexity to improve accuracy. This study aims to estimate the risk of government bonds based on the estimation of bond prices with the effect of convexity. Several studies have shown that exponential duration can predict bond prices more accurately than Macau duration. Exponential duration with convexity will be applied in this study to measure the accurate value of bond prices caused by changes in interest rates. The Delta-Normal VaR portfolio method is used to calculate risk based on estimated bond prices in the form of a portfolio. The formation of this portfolio aims to reduce the losses suffered by investors. This method is applied to four Indonesian government bonds with codes FR0056, FR0059, FR0074, and FR0080. The results showed that the bonds portfolio FR0056 and FR0074 had the smallest risk compared to other portfolios with a weight proportion of 15% for bonds FR0056 and 85% for bonds FR0074.